(untitled) (American Journal of Youth and Women Empowerment, 2025)
The global goal of empowering women in various economic activities is essential in achieving the overarching objective of poverty reduction and sustainable economic development. The goal of current study was to assess the contribution of women entrepreneurs in poverty reduction at household level at Arumeru District in Arusha region. The specific of this study was to identify different activities performed by women entrepreneurs in Arumeru district, to find out challenges facing women entrepreneurs in Meru ward and to examine the contribution of women entrepreneurs in reducing household’s poverty. The study used both primary and secondary data and different methods used in collecting those data such as interview, questionnaire, observation and documentation and focus group discussion. A sample of 30 respondents was selected for the study including Municipal Development Officer, Ward Executive Officer and Women entrepreneur. The Researcher used MS Excel to conduct data analysis. The findings revealed that the activities that are done by women entrepreneurs in Meru District include food vendors, tailoring, charcoal sellers, loan provisions, shopkeepers and hand crafts design that could lead them to generate their own income. The contribution of women entrepreneurs in reducing house hold income poverty because it helps them to support family needs such as to pay school fees for their children. The study came out with the challenges which face women in entrepreneur which lead them to fail in their development plans such as limited access to credit. Based on the findings, several government and other stakeholders should inject their progressive and sustainable interventions to foster women participation and engagement in entrepreneurship activities and take actions to facilitate in overcoming the challenges facing their activities by improving credit and market accessibility.